2015
DOI: 10.1016/j.agwat.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal effectiveness by riparian buffer zones in rural temperate watersheds: The impact of no-till crops practices

Abstract: a b s t r a c tRiparian buffer zones have the potential to capture chemical contaminants and to mitigate detrimental side-effects in aquatic ecosystems derived from excess fertilizers used in agro-food production. No-till farming systems are well known agricultural practices and are widely used in temperate areas. In that regard, different settings and widths of riparian buffer zones (12, 24, 36, 48 and 60 m) with woody vegetation, shrubs or grasses were assessed. The methodology was comprised of the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 31 publications
2
25
0
5
Order By: Relevance
“…Soils with woody vegetation have a higher content of organic matter than soils with grass and shrubs because of the leaves and wood deposited and degraded in the soils [51]. Indeed, 60-m-wide buffers composed of woody soils were more effective in N removal (99.9%) than areas with shrub (83.9%) or grass vegetation (61.6%) [52]. For nitrate however, 20-m-wide woody vegetation showed a good capacity for removing pollutants (65%), while the riparian zone composed of shrubs and grasses did not show good results [53,54].…”
Section: Effect Of Width On the Retention Capacity Of Riparian Buffermentioning
confidence: 99%
“…Soils with woody vegetation have a higher content of organic matter than soils with grass and shrubs because of the leaves and wood deposited and degraded in the soils [51]. Indeed, 60-m-wide buffers composed of woody soils were more effective in N removal (99.9%) than areas with shrub (83.9%) or grass vegetation (61.6%) [52]. For nitrate however, 20-m-wide woody vegetation showed a good capacity for removing pollutants (65%), while the riparian zone composed of shrubs and grasses did not show good results [53,54].…”
Section: Effect Of Width On the Retention Capacity Of Riparian Buffermentioning
confidence: 99%
“…Further, the pollutant‐trapping potential of buffer strips can range from 50 to 98% for suspended solids (Rudra & Whiteley ), 70–98% for phosphorus and 70–95% for nitrate (Aguiar et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…slope, size, land use) and the plant composition of the buffer strips (herbaceous, woody or both) (Yuan et al 2009). Further, the pollutant-trapping potential of buffer strips can range from 50 to 98% for suspended solids (Rudra & Whiteley 2000), 70-98% for phosphorus and 70-95% for nitrate (Aguiar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The effects range from skin lesions to cancers, tumors, immune system suppression, DNA damage, reproductive impairment, physical deformities, to death of the organism (Hashmi et al 2011;Damalas and Eleftherohorinos 2011). Andreoli (1993) and Aguiar et al (2014Aguiar et al ( , 2015 reports that by 1970, Brazil had become the world's third largest user of pesticides, only exceeded by France and the USA, but less than 15 % of the active ingredients marketed in Brazil were analyzed. From 1976 to 1984, a study of 17 substances, among them 11 organochlorine pesticides in the Paraná River basin, found that 91.4 % of ambient samples contained at least one.…”
Section: Introductionmentioning
confidence: 99%